A new method for the prediction of diffusion coefficients in poly(ethylene terephthalate)—Validation data. Issue 5 (23rd January 2022) - Ewender, Johann; Welle, Frank
Abstract : Prediction of the migration is a useful tool in compliance evaluation of food contact materials. In our previous work, such a prediction model had been established for polyethylene terephthalate (PET), which is widely used as packaging material for beverages as well as for meat and cheese. Within the actual study, 263 diffusion coefficients in PET for 66 substances at temperatures between 40°C and 120°C were determined from permeation kinetic experiments. The diffusion coefficients D P were compared with the predicted values by use of a log/log plot as well as in direct comparison of the diffusion coefficients. When applying the migration prediction model for compliance evaluation of food packaging materials, it is mandatory that the migration prediction is over‐estimative in any case. As a result, the predicted values are in good agreement with the experimental results. The prediction model slightly over‐estimates the real migration by a factor of 1.3 in average. Reduction of the molecular volume of 20% results in an average over‐estimation of 3 of the migration (worst‐case). Another finding of this study is that the diffusion behaviour at the glass transition temperature not significantly change. The prediction model is applicable below and above the glass transition temperature. Abstract : Prediction of diffusion coefficients D P in polyethylene terephthalate (PET) is useful for migration and exposure evaluation of PET packed food and beverages. Overall, 263 diffusion coefficients for 66 substances were determined and compared to predicted values. The predicted diffusion coefficients are in good agreement with the experimental results.